Stacking sequence effects on flexural stiffness, failure progression, and energy absorption in asymmetric CFRP laminates - Afsar Husain; Sanan H. Khan; Abdel Hamid I. Mourad (Results in Engineering, 2025)
This study investigates the fabrication, flexural behavior, failure mechanisms, and energy absorption characteristics of asymmetric composite laminates through experimental testing and finite element modeling. Six distinct asymmetric configurations of carbon fiber reinforced epoxy laminates (CFRP) were examined to explore the relationships between layout design, mechanical properties, and damage progression. Three-point bending tests were conducted to evaluate the flexural properties of each configuration. A finite element model was developed using ABAQUS, incorporating a user-defined material subroutine to capture the complex damage behavior of the asymmetric laminates. The results demonstrate that the stacking sequence significantly influences the flexural behavior of asymmetric laminates. Configurations with strategically placed 0° plies on outer surfaces exhibited superior load-bearing capacity, while layups incorporating ±45° plies showed enhanced progressive failure characteristics. Energy absorption analysis revealed configuration dependent patterns, with stacking sequence of [0°2/+45°/90°2/-45°/0°2] showing an early onset of delamination and fiber energy absorption, while stacking sequence [0°4/30°2/60°2] and [0°3/+45°/-45°/90°3] demonstrated more gradual matrix energy absorption. Finite element analysis revealed a transition from localized delamination in simpler layups to distributed, multi-interface failures in complex configurations. The postmortem examination confirmed various failure modes, including fiber failure, matrix cracking, delamination, and fiber pull-out. Analysis of out-of-plane stress distributions showed variations from gradual increases to steep gradients, while deformation profiles ranged from stiff to compliant responses. These findings provide valuable insight for optimizing asymmetric laminates for specific loading conditions and energy absorption requirements in various engineering applications.